PENINGKATAN LITERASI SAINS MENGGUNAKAN METODE PROBLEM BASED LEARNING BERBASIS PEMBELAJARAN SMART CLASSROOM PADA MATA KULIAH ILMU ALAMIAH DASAR - Harkam Tujantri; Titis Wulandari; Oktavian Dwi Prasetyo; Nico Wahyu Saputra (LP3M Universitas Muhammadiyah Muara Bungo, 2022)
Literacy is an activity that aims to obtain information through activities, reading, writing, listening and explaining. Through scientific literacy, it is expected to be able to facilitate the understanding of learning. This study aims to determine students' scientific literacy skills by applying a Problem-based learning model based on Smart Classroom learning in Basic Natural Sciences. This study uses qualitative and quantitative methods, the research sample is 21 students of PJKR STKIP Muhammadiyah Muara Bungo. Data collection techniques using test and non-test instruments and statistical tests were carried out. The results of the research on the mean pre-test and post-test in the class before the lecture was held in the smart classroom mean 70 and after being implemented in the classroom mean 87, this has increased quite effectively, it is known that the N-gain value has no value (negative) meaning that there is an increase from pretest to posttest conditions. This is an increase in students' scientific literacy abilities after receiving PBL learning in the Smart Classroom. The results of the non-test instrument of lecture activities carried out in the smart classroom can affect student learning outcomes, where the results of the questionnaire state that many students are more focused in attending lectures and students are more active in the lecture process. The increase that occurred after going through the PBL model learning using the lecture room in the smart classroom was quite effective.